2011
DOI: 10.1371/journal.pone.0022623
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Profiles of Growth Factor Expression during CNS Demyelination Reveal the Dynamics of Repair Priming

Abstract: Demyelination is the cause of disability in various neurological disorders. It is therefore crucial to understand the molecular regulation of oligodendrocytes, the myelin forming cells in the CNS. Growth factors are known to be essential for the development and maintenance of oligodendrocytes and are involved in the regulation of glial responses in various pathological conditions. We employed the well established murine cuprizone model of toxic demyelination to analyze the expression of 13 growth factors in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
94
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 57 publications
11
94
2
3
Order By: Relevance
“…Consistent with previous reports (38), WT mice showed a peak of microgliosis at 4 weeks which hinders subsequent myelin regeneration. This conclusion was supported by immunohistochemical analysis of ODC.…”
Section: Trem2 Is Required For Myelin Debris Removal and Remyelinatiosupporting
confidence: 92%
“…Consistent with previous reports (38), WT mice showed a peak of microgliosis at 4 weeks which hinders subsequent myelin regeneration. This conclusion was supported by immunohistochemical analysis of ODC.…”
Section: Trem2 Is Required For Myelin Debris Removal and Remyelinatiosupporting
confidence: 92%
“…We found upregulation of Pdgfa, Pdgfb, Vegfa, Vegfb, Tgfb1, Igf1, and Spp1, all of which have been reported to promote oligodendrocyte differentiation (Baumann and Pham-Dinh, 2001;Bradl and Lassmann, 2010;Chesik et al, 2008;Diemel et al, 2003;Frost et al, 2003;Hinks and Franklin, 1999;Hsieh et al, 2004;Kim et al, 2009;Selvaraju et al, 2004;Vela et al, 2002;Woodruff et al, 2004). Interestingly, we did not find upregulation of Gdnf or Fgf2, as reported by Gudi et al (2011). In their study, Gdnf induction in microglia peaked at 1 week of cuprizone treatment after which it abruptly declined, whereas the highest expression of Fgf2 was observed at 3.5 weeks of demyelination.…”
Section: Discussionsupporting
confidence: 58%
“…Hu et al [27] concluded that FGF-2 was important as an initial regulator of neovascularisation, and VEGF may be important during later phases of angiogenesis. In some neurological disorders, it was reported that microglia was one source of FGF-2 [46,47] . There are no studies so far that document whether microglial cells produce FGF-2 in AMD.…”
Section: Discussionmentioning
confidence: 99%